Testing the Engel's Law in the Consumption Pattern of Romanian Population - Neagu, Mădălin Ioan; Teodoru, Mircea Constantin (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
The aim of the paper is to test the valability of Engel's law in the Romanian consumption dynamics after 1990. We used NIS ad EUROSTAT data to interpret the dynamics of the households' income and consumption expenditures and its structure by destinations. We explored the relationship between consumption and income through the regression analysis and found that the Engel's law applies in the Romanian economy, since 1990 to 2016, with specific evolutions and influences.